The Data Set : The Sky Is Falling - Ada Hopper (India Simon Spotlight, 2016)
When bizarre lights streak across the night sky, everyone in Newtonburg has a theory, but the DATA Set knows who is to blame: Dr. Bunsen. This time his newest invention speaks to aliens$1! =(Band invites them down to Earth! Can the kids handle a close encounter with extraterrestrials and mysterious men in black to keep their town from being space-invaded?s
Keywords: Science Fiction